ANALISIS LINGKUNGAN EKONOMI DALAM PEMASARAN INTERNASIONAL - Sinaga, Afdillah Nur Aisyah; Suhairi, Suhairi; Melati, Melati; Pratiwi, Ayu Intan (Bussman Journal : Indonesian Journal of Business and Management, 2023)
Understanding related to the economic environment of a country is very important if you want to carry out product marketing activities internationally. If marketing activities do not pay attention to the economic environment of a country, it will experience obstacles in marketing its exported products. In this research, it will be explained and analyzed what economic environmental factors are very important to know and understand before exporting products and marketing products on an international scale to countries that are the target market of the company. This research uses a qualitative methodology by collecting data from literal studies through secondary data which is carried out with a literature review concluding an article. Based on the results of this study, to carry out marketing on a global scale, companies must analyze indicators of the economic environment of a country which is the target market for a product that will be sold by the company. The indicators of the economic environment include economic structure, economic growth, inflation, interest rates, tax rates, exchange rates, consumer confidence levels and unemployment rates